Benchmarking the power of amateur observatories for TTV exoplanets detection. Issue 3 (9th May 2015) - Baluev, Roman V.; Sokov, Evgenii N.; Shaidulin, Vakhit Sh.; Sokova, Iraida A.; Jones, Hugh R. A.; Tuomi, Mikko; Anglada-Escudé, Guillem; Benni, Paul; Colazo, Carlos A.; Schneiter, Matias E.; D'Angelo, Carolina S. Villarreal; Burdanov, Artem Yu.; et al.
Abstract : We perform an analysis of ∼80 000 photometric measurements for the following 10 stars hosting transiting planets: WASP-2, -4, -5, -52, Kelt-1, CoRoT-2, XO-2, TrES-1, HD 189733, GJ 436. Our analysis includes mainly transit light curves from the Exoplanet Transit Database, public photometry from the literature, and some proprietary photometry privately supplied by other authors. Half of these light curves were obtained by amateurs. From this photometry we derive 306 transit timing measurements, as well as improved planetary transit parameters. Additionally, for 6 of these 10 stars we present a set of radial velocity measurements obtained from the spectra stored in the HARPS, HARPS-N and SOPHIE archives using the HARPS–TERRA pipeline. Our analysis of these transit timing and radial velocity data did not reveal significant hints of additional orbiting bodies in almost all of the cases. In the WASP-4 case, we found hints of marginally significant TTV signals having amplitude 10–20 s, although their parameters are model dependent and uncertain, while radial velocities did not reveal statistically significant Doppler signals.